2023
DOI: 10.1002/cpt.3077
|View full text |Cite
|
Sign up to set email alerts
|

Tacrolimus Pharmacokinetics is Associated with Gut Microbiota Diversity in Kidney Transplant Patients: Results from a Pilot Cross‐Sectional Study

Alexandra L. Degraeve,
Laure B. Bindels,
Vincent Haufroid
et al.

Abstract: Clinical use of tacrolimus, an essential immunosuppressant following transplantation, is complexified by its high pharmacokinetic variability. The gut microbiota gains growing interest but limited investigations have evaluated its contribution to tacrolimus pharmacokinetics. Here, we explore the associations between the gut microbiota composition and tacrolimus pharmacokinetics. In this pilot cross‐sectional study (Clinicaltrial.gov NCT04360031), we recruited 93 CYP3A5 non‐expressers stabilized kidney transpla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 52 publications
(116 reference statements)
0
0
0
Order By: Relevance
“…Tacrolimus pharmacokinetics is associated with gut microbiota diversity in kidney transplant patients as resulted from a pilot cross-sectional study by Degraeve et al [ 44 ].…”
Section: Gut Microbiota Modification Induced By Immunosuppressive Drugsmentioning
confidence: 99%
“…Tacrolimus pharmacokinetics is associated with gut microbiota diversity in kidney transplant patients as resulted from a pilot cross-sectional study by Degraeve et al [ 44 ].…”
Section: Gut Microbiota Modification Induced By Immunosuppressive Drugsmentioning
confidence: 99%
“…Tacrolimus, a macrolide antibiotic-type calcineurin inhibitor, has immunosuppressive effects that are 10 to 100 times stronger than CsA, both in vivo and in vitro, making it a first-line medication for anti-rejection therapy and treating recurrent IgAN post-kidney transplantation. A cross-sectional study has shown that the pharmacokinetics of tacrolimus are closely linked to the variety of the gut microbiome in patients with kidney transplants [ 143 ]. This implies that although previous research suggested genetic polymorphisms (such as gene mutations) influence the pharmacokinetics parameters of tacrolimus to some extent [ 144 ], it is now recognized that the composition and diversity of the gut microbiome are also significant factors.…”
Section: The Current Status Of Recurrent Igan Post-kidney Transplanta...mentioning
confidence: 99%